Postoperative Low-Dose Tranexamic Acid After Major Spine Surgery: A Matched Cohort Analysis - Lauren K. Dunn; Ching-Jen Chen; Davis G. Taylor; Kamilla Esfahani; Brian Brenner; Charles Luo; Thomas J. Buell; Sarah N. Spangler; Avery L. Buchholz; Justin S. Smith; Christopher I. Shaffrey; Edward C. Nemergut; et al. (Neurospine, 2020)
Objective This was a retrospective, cohort study investigating the efficacy and safety of continuous low-dose postoperative tranexamic acid (PTXA) on drain output and transfusion requirements following adult spinal deformity surgery. Methods One hundred forty-seven patients undergoing posterior instrumented thoracolumbar fusion of ≥ 3 vertebral levels at a single institution who received low-dose PTXA infusion (0.5–1 mg/kg/hr) for 24 hours were compared to 292 control patients who did not receive PTXA. The cohorts were propensity matched based on age, sex, American Society of Anesthesiologist physical status classification, body mass index, number of surgical levels, revision surgery, operative duration, and total intraoperative TXA dose (n = 106 in each group). Primary outcome was 72-hour postoperative drain output. Secondary outcomes were number of allogeneic blood transfusions. Results There was no significant difference in postoperative drain output in the PTXA group compared to control (660 ±420 mL vs. 710 ±490 mL, p = 0.46). The PTXA group received significantly more crystalloid (6,100 ±3,100 mL vs. 4,600 ±2,400 mL, p < 0.001) and red blood cell transfusions postoperatively (median [interquartile range]: 1 [0–2] units vs. 0 [0–1] units; incidence rate ratio [95% confidence interval], 1.6 [1.2–2.2]; p = 0.001). Rates of adverse events were comparable between groups. Conclusion Continuous low-dose PTXA infusion was not associated with reduced drain output after spinal deformity surgery. No difference in thromboembolic incidence was observed. A prospective dose escalation study is warranted to investigate the efficacy of higher dose PTXA.